Marital Satisfaction and a Sense of Life’s Meaning Among Couples Struggling with Infertility. A Theological-Pastoral Take - Goleń, Jacek (Verbum Vitae, 2020)
The problem of infertility today constitutes a challenge for pastoral theology and pastoral care of families. This article, of a theological-empirical character, addresses the correlation between marital satisfaction and a sense of life’s meaning among infertile married couples who seek help in Catholic clinics for infertility treatment. It first discusses the theoretical background and selected results of existing scholarship on the influence that infertility has on conjugal relations and a sense of life’s meaning. Then, it outlines the group of infertile married individuals studied and elucidates the research methodology employed. Then, the results of the research into a sense of life’s meaning and marital satisfaction are presented, together with the correlation between the two factors. The final section of the article offers conclusions drawn from the research conducted. The article argues that a sense of life’s meaning is visibly contingent on the respondents’ martial satisfaction, especially on their working together on their problems and leading trustful conversations about them, on their care for strengthening their mutual love, and on showing the spouse that they are loved. On this basis, the article argues that pastoral care offered to infertile couples needs to enhance their faith, which will have a positive impact on their sense of life’s meaning and on their marital satisfaction. Both within regular work at clinics for infertility diagnosis and treatment and within pastoral care, infertile couples should be taught to show care for their mutual bond, especially to have conversations that will enable them to manifest and strengthen their love and solve problems, as this would foster their marital satisfaction and enhance their sense of life’s meaning.